Secondary raw material markets in the C&D sector: Study on user acceptance in southwest Germany - Rebekka Volk; Christian Frederik Kern; Frank Schultmann (Karlsruhe Institute of Technology (KIT), Institute for Industrial Production (IIP), 2020)
In industrialized countries, regulations demand increasingly higher recycling (RC) rates and many efforts are undertaken to recycle construction and demolition (C&D) waste fractions. The C&D sector has indisputable relevance due to the highest mineral waste fraction, high numbers of employees and turnovers. High-quality RC construction products can be produced to sub-stitute primary resources and reduce land use. This empirical study analyses the acceptance of RC materials in Germany particularly of private awarding authorities in their private construction project(s). In 41 structured interviews, data is collected and evaluated based on hypotheses. Qualitative and quantitative analyses show that acceptance problems cannot be stated. However, medium knowledge and low experience with RC construction materials as well as communication problems are identified. The respondents have no concerns and tend to trust in RC construction materials, but this is decreasing with the increased structural importance of the materials. Surprisingly, quality is the most frequently mentioned decision criteria in private construction projects, followed by cost. Private awarding authorities see no increase of their property value by using RC construction materials. And, the majority is unwilling to pay a premium for RC construction materials. Higher material quality standards, regular government reviews and financial support are seen conducive.
Keywords: 330; recycling construction materials; C&D sector; secondary raw materials; acceptance; private awarding authorities